Prevalence and factors associated with adverse birth outcomes among women with chronic hypertension in Rangpur: A multi-center cross-sectional study - Azaz Bin Sharif; Syed Sharaf Ahmed Chowdhury; Md. Zakir Hossain; Md. Anwar Hossain; Ahmed Hossain; Hasan Mahmud Reza (PLoS ONE, 2025)
Background Hypertension affects approximately 3–5% of pregnancies globally, with an increased risk of adverse birth outcomes (ABOs) among mothers with chronic hypertension, which poses a significant public health challenge. Despite global evidence, there is a lack of studies in Bangladesh specifically investigating the impact of chronic hypertension on birth outcomes. Therefore, the study aims to find the prevalence and factors associated with adverse birth outcomes among women with chronic hypertension who delivered in health facilities. Methods An institution-based multi-center cross-sectional study was conducted in 3 different maternity and child hospitals in Rangpur City between June 2023 and September 2023 and recruited 342 hypertensive females who gave birth in an institutional setting within the last 6 months. The outcome variable was the adverse birth outcomes. For the statistical analysis, STATA version 17.0 was used. Descriptive analysis, Pearson’s chi-square test, and both the bivariable and multivariable binary logistic regression analyses were conducted to determine the association between birth outcomes and covariates. Result The overall prevalence of adverse birth outcomes among the study participants was 36% (95% CI: 30.87, 41.30). Among the study participants, mothers belonging to a family with higher income (AOR: 3.09; 95% CI: 1.51, 6.30), participants with complicated pregnancies (AOR: 2.55; 95% CI: 1.55, 4.21), mothers who had at least one danger sign present in their last pregnancy (AOR: 2.21; 95% CI: 1.17, 4.15), exposure to secondhand smoke during their pregnancy (AOR: 3.33; 95% CI: 1.16, 9.60) were significantly associated with adverse birth outcomes among hypertensive pregnant women. Conclusion This study observed a high prevalence of adverse birth outcomes among pregnant women with chronic hypertension who had an institutional delivery. The finding warrants immediate community-based action focused on the important factors to reduce adverse birth outcomes among hypertensive mothers. Further longitudinal studies are needed to identify any causal association between important variables and adverse birth outcomes.